The intended mathematics curriculum as represented in state-level curriculum standards : consensus or confusion? - Reys, Barbara J. (Emerald Publishing Limited : Information Age Pub., 2006)
This volume represents a detailed analysis of the grade placement of mathematics learning goals across all state-level curriculum standards published as of May 2005. The volume documents the varied grade-level mathematics curriculum expectations in the U.S. and highlights a general lack of consensus across states. As states continue to work to improve learning opportunities for all students this report can serve as a useful summary to inform future curriculum decisions. The report is also intended to stimulate discussion at the national level regarding roles and responsibilities of national agencies and professional organizations with regard to curriculum leadership. Serious and collaborative work that results from such discussions can contribute to a more coherent, focused mathematics curriculum for US students.
Keywords: Mathematics -- Study and teaching -- United States.; Education -- Standards -- United States.; Curriculum evaluation -- United States.; Education -- Curricula.; Educational: Mathematics and numeracy.; Curriculum planning and development.; elektronické knihy; electronic books